Modélisation de problèmes non linéaires de grande taille : grandes déformations et autocontact dans un milieu cellulaire - Barboteu, Mikaël; Alart, Pierre; Pagano, Stéphane (European Journal of Computational Mechanics, 2002)
The paper presents a numerical modelling of the non linear behaviour of a cellular medium submitted to strong loadings. Efficient numerical tools are performed. The non linearities are issued from finite deformations and self-contact conditions involving in the cellular network with thin walls. The non linear solver is based on a generalized Newton method which deals simultaneously with the two non linearities. The linearized system is solved by a domain decomposition method adapted to contact and friction. The numerical simulations using increasing size samples underline the microbuckling phenomenae and the influence of the contact condition on the localization process characterized by shear bands.